The prevalence of nine genetic disorders in a dog population from Belgium, the Netherlands and Germany. - Bart J G Broeckx (Public Library of Science (PLoS), 2013)
The objective of this study was to screen a dog population from Belgium, the Netherlands and Germany for the presence of mutant alleles associated with hip dysplasia (HD), degenerative myelopathy (DM), exercise-induced collapse (EIC), neuronal ceroid lipofuscinosis 4A (NCL), centronuclear myopathy (HMLR), mucopolysaccharidosis VII (MPS VII), myotonia congenita (MG), gangliosidosis (GM1) and muscular dystrophy (Duchenne type) (GRMD). Blood samples (K3EDTA) were collected for genotyping with Kompetitive Allele Specific PCR (n = 476). Allele and genotype frequencies were calculated in those breeds with at least 12 samples (n = 8). Hardy-Weinberg equilibrium was tested. Genetic variation was identified for 4 out of 9 disorders: mutant alleles were found in 49, 15, 3 and 2 breeds for HD, DM, EIC and NCL respectively. Additionally, mutant alleles were identified in crossbreeds for both HD and EIC. For HD, DM, EIC and NCL mutant alleles were newly discovered in 43, 13, 2 and 1 breed(s), respectively. In 9, 2 and 1 breed(s) for DM, EIC and NCL respectively, the mutant allele was detected, but the respective disorder has not been reported in those breeds. For 5 disorders (HMLR, MPS VII, MG, GM1, GRMD), the mutant allele could not be identified in our population. For the other 4 disorders (HD, DM, EIC, NCL), prevalence of associated mutant alleles seems strongly breed dependent. Surprisingly, mutant alleles were found in many breeds where the disorder has not been reported to date.